2017
DOI: 10.1038/s41467-017-02171-2
|View full text |Cite
|
Sign up to set email alerts
|

Gli1 identifies osteogenic progenitors for bone formation and fracture repair

Abstract: Bone formation in mammals requires continuous production of osteoblasts throughout life. A common molecular marker for all osteogenic mesenchymal progenitors has not been identified. Here, by lineage-tracing experiments in fetal or postnatal mice, we discover that Gli1+ cells progressively produce osteoblasts in all skeletal sites. Most notably, in postnatal growing mice, the Gli1+ cells residing immediately beneath the growth plate, termed here “metaphyseal mesenchymal progenitors” (MMPs), are essential for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
318
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(334 citation statements)
references
References 40 publications
(35 reference statements)
16
318
0
Order By: Relevance
“…Recent studies have used inducible Cre reporter mice to track osteoblast lineage cells in skeletal development and fracture repair . Osteoblasts are derived from mesenchymal progenitor cells, which differentiate into osteoprogenitors (or preosteoblasts), and then mature osteoblasts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have used inducible Cre reporter mice to track osteoblast lineage cells in skeletal development and fracture repair . Osteoblasts are derived from mesenchymal progenitor cells, which differentiate into osteoprogenitors (or preosteoblasts), and then mature osteoblasts .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have used inducible Cre reporter mice to track osteoblast lineage cells in skeletal development and fracture repair. (10)(11)(12)(13)(14)(15) Osteoblasts are derived from mesenchymal progenitor cells, which differentiate into osteoprogenitors (or preosteoblasts), and then mature osteoblasts. (16) The cells of the osteoblast lineage responsible for bone formation can be well-visualized on the periosteal surface of the tibia.…”
Section: Introductionmentioning
confidence: 99%
“…SSCs are endogenous stem cells in skeletal tissues. Increasing evidence has demonstrated that SSCs are closely involved in bone homeostasis . These cells respond to tissue stress and migrate to sites of injury, supplying new osteoblasts during fracture healing .…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal stem cells (SSCs) have been defined as tissue-specific stem cells in skeletons and have been demonstrated to play pivotal roles in maintaining and repairing skeletal tissues. [1][2][3][4][5][6][7][8] By determining unique cell surface maker profiles and performing rigorous functional characterizations, previous researchers have identified a number of subpopulations of stem and progenitor cells from skeletal tissues, including bone, cartilage, and tendon. [1][2][3][4][5][6][7][8] Chan et al showed the presence of CD45-Ter119-Tie2-AlphaV+ multipotent stem cells in murine bone and identified cells and factors in the SSC niches that regulate its activity.…”
Section: Introductionmentioning
confidence: 99%
“…Ihh regulates osteogenic differentiation by modulating Runx2‐controlled osteoblastic cell fates . Gli1‐positive cells located beneath the growth plate contribute to both chondrocytes and osteoblasts during bone fracture healing . Ihh signaling also plays a critical role in osteoblast differentiation by regulating Runx2 and Runx3 activity .…”
Section: Introductionmentioning
confidence: 99%